2022
DOI: 10.1108/maj-06-2021-3210
|View full text |Cite
|
Sign up to set email alerts
|

Key audit matters and debt contracting: evidence from China

Abstract: Purpose In an effort to make audit reports more informative to users, the Public Company Accounting Oversight Board and the International Auditing and Assurance Standards Board adopted a standard that requires auditors to disclose key audit matters (KAMs). This paper aims to explore the impact of the risk information provided by KAMs on corporate debt contracting. Design/methodology/approach In China, the KAM standard went into effect for A + H cross-listing companies in 2017 and became mandatory for all lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Audit expectation gap; creditors’ benefits and perceptions; investors’ reactions and perceptions; and financial analysts’ forecasts and perceptions are variables that form the third group of EAR consequences, i.e. auditee-stakeholder relationship (Hatherly et al , 1991; Innes et al , 1997; Liu et al , 2022; Rapley et al , 2021; Gutierrez et al , 2018; Venturini et al , 2022; Hu et al , 2022). Following the agency, stakeholders and legitimacy theories, some results of these studies imply that improving the audit report transparency through EAR can reduce the expectations gap, information asymmetry and possible conflicts of interest between management and shareholders and increase the stakeholders’ trust and the company’s legitimacy (Suttipun, 2022; Fuller, 2015).…”
Section: Results Of Content Analysismentioning
confidence: 99%
“…Audit expectation gap; creditors’ benefits and perceptions; investors’ reactions and perceptions; and financial analysts’ forecasts and perceptions are variables that form the third group of EAR consequences, i.e. auditee-stakeholder relationship (Hatherly et al , 1991; Innes et al , 1997; Liu et al , 2022; Rapley et al , 2021; Gutierrez et al , 2018; Venturini et al , 2022; Hu et al , 2022). Following the agency, stakeholders and legitimacy theories, some results of these studies imply that improving the audit report transparency through EAR can reduce the expectations gap, information asymmetry and possible conflicts of interest between management and shareholders and increase the stakeholders’ trust and the company’s legitimacy (Suttipun, 2022; Fuller, 2015).…”
Section: Results Of Content Analysismentioning
confidence: 99%
“…This study argued that the transparency of audit reports might widen the audit expectation gap if the information available is not in the correct context (Segal, 2019;Liu, Ning, Zhang, & Zhang, 2022). The study found that the displayed accounting estimates as part of the KAM do not enhance the decision-usefulness of accounting information (Lau, 2021).…”
Section: Liability Of Auditorsmentioning
confidence: 90%
“…Conversely, Zeng et al (2021) found that China's KAMs are not overwhelmed by boilerplate text. Liu et al (2022) find that KAMs disclosures in China decrease the interest rate and increase the proportion of long-term debt by improving the information environment.…”
Section: 3mentioning
confidence: 93%